BitTorious volunteer: server-side extensions for centrally-managed volunteer storage in BitTorrent swarms. Issue 1 (December 2015) - Lee, Preston; Dinu, Valentin
Abstract Background Our publication of the BitTorious portal [1] demonstrated the ability to create a privatized distributed data warehouse of sufficient magnitude for real-world bioinformatics studies using minimal changes to the standard BitTorrent tracker protocol. In this second phase, we release a new server-side specification to accept anonymous philantropic storage donations by the general public, wherein a small portion of each user's local disk may be used for archival of scientific data. We have implementated the server-side announcement and control portions of this BitTorrent extension into v3.0.0 of the BitTorious portal, upon which compatible clients may be built. Results Automated test cases for the BitTorious Volunteer extensions have been added to the portal's v3.0.0 release, supporting validation of the "peer affinity" concept and announcement protocol introduced by this specification. Additionally, a separate reference implementation of affinity calculation has been provided in C++ for informaticians wishing to integrate intolibtorrent -based projects. Conclusions The BitTorrent "affinity" extensions as provided in the BitTorious portal reference implementation allow data publishers to crowdsource the extreme storage prerequisites for research in "big data" fields. With sufficient awareness and adoption of BitTorious Volunteer-based clients by the general public, the BitTorious portal may be able to provide peta-scale storage resources to the scientific community at relatively insignificant financial cost.